Exploring the role of Chinese culture on the perception and motivation of Organizational Citizenship Behavior (OCB) - Wong, Yuk Ki Mark (2009)
Organizational Citizenship Behavior describes a type of discretionary work behavior adopted by an employee to perform tasks that is outside his formal job role. There are two main perspectives to explain why employee performs OCB. The main perspective from the literature suggests employee performs OCB as a reaction to good organizational treatments. The second theoretical framework points out that employee perform OCB due to a combination of motives. This dissertation considers the role of cultural context in this theoretical debate of OCB. Using in-depth interviews, it explores the role of Chinese culture on the perception and motivation of this specific type of discretionary work behavior. The theoretical implications on mainstream theories and other managerial implications are discussed.